Sistem Informasi Perkiraan Produksi Kopi Robusta di Perusahaan Daerah Perkebunan Jember - Murtadho, Ali; Marimin; Kasutjaningati (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Taxation process was used to determine coffee production target at Jember District Own Company-Estate. Taxation was conducted to count the number of coffee beeds in one particular plant. However, the use of taxtion in recent years has shown less-accurate counting result. It did not include the factors influencing the coffee production, such as the climate. The objective of this research was to design an Information System for determining the coffee beeds production. This system was able to help in determining the entire coofee production. The system was supported by forecasting process through double exponential smoothing by using the production data of the last 5 years. Information System employs rule base in determining the suitability by using 8 parameters. The determination of coffee production, land suitability, and inserting 23 parameters of plant treatment were processed using rule based inference system. The results of this research revealed that system accuration level migth be reached when a company performed factual data input. There was a significant gap between the data which used double exponential smoothing and Information System output. It was found that the quetionnaire-filling process was critical and must be supported by accurate data. Experts suggested that coffee production might be made to maximum level by optimazing the factors to determine coffee production. Keywords: coffee production, robusta coffee, forecasting, rule based system